Efficient Inverted Planar Perovskite Solar Cells Using Ultraviolet/Ozone‐Treated NiOx as the Hole Transport Layer. Issue 6 (28th March 2019) - Wang, Tun; Ding, Dong; Zheng, Hao; Wang, Xin; Wang, Jiayuan; Liu, Hong; Shen, Wenzhong
Abstract : Nickel oxide (NiOx ) has exhibited great potential as a hole transport layer (HTL) for fabricating efficient and stable perovskite solar cells (PSCs). However, it has been greatly limited by its fabrication and manipulation process. In this work, a simple processing method on an ultrathin electrochemical mesoporous NiOx film manipulated by controllable ultraviolet/ozone (UVO) treatmentis employed; the duration of UVO treatment on the NiOx film significantly affects the photovoltaic properties of the PSCs. When the exposure duration increases, the wettability, electrical conductivity, nonstoichiometry, and valence band energy of the NiOx film are improved with varying degrees. Besides, the perovskite grain size, recombination resistance at the perovskite/NiOx interface, and build‐in potential of the device also increase, resulting in higher short‐circuit current density ( J SC ) and open‐circuit voltage ( V OC ). Combining these factors together, an optimal exposure time of UVO treatment on the NiOx film has been achieved at 5 min, which results in a significantly high performance with an efficiency of 19.67%, large V OC (>1.1 V), and J SC (>23 mA cm −2 ). Furthermore, the experimental results are coincide well with simulation results on the different corresponding subjects. Hopefully, this work could facilitate material manipulation toward scalable, high efficiency, and stable solar cells. Abstract : A controllable ultraviolet/ozone (UVO) treatment is employed to prepare a high‐quality electrochemically deposited NiOx hole transport layer (HTL). Under optimal conditions of UVO treatment, the increased hole conductivity in the HTL reduces defects at the HTL/perovskite interface, and a narrowed offset of the valence band between the HTL and perovskite film are obtained, which results in high‐performance perovskite solar cells with an efficiency of 19.67%.